Choose Your Weapon: Defensive Behavior Is Associated with Morphology and Performance in Scorpions - van der Meijden, Arie; Lobo Coelho, Pedro; Sousa, Pedro; Herrel, Anthony (PLOS ONE, 2013)
Morphology can be adaptive through its effect on performance of an organism. The effect of performance may, however, be modulated by behavior; an organism may choose a behavioral option that does not fully utilize its maximum performance. Behavior may therefore be decoupled from morphology and performance. To gain insight into the relationships between these levels of organization, we combined morphological data on defensive structures with measures of defensive performance, and their utilization in defensive behavior. Scorpion species show significant variation in the morphology and performance of their main defensive structures; their chelae (pincers) and the metasoma (“tail”) carrying the stinger. Our data show that size-corrected pinch force varies to almost two orders of magnitude among species, and is correlated with chela morphology. Chela and metasoma morphology are also correlated to the LD50 of the venom, corroborating the anecdotal rule that dangerously venomous scorpions can be recognized by their chelae and metasoma. Analyses of phylogenetic independent contrasts show that correlations between several aspects of chela and metasoma morphology, performance and behavior are present. These correlations suggest co-evolution of behavior with morphology and performance. Path analysis found a performance variable (pinch force) to partially mediate the relationship between morphology (chela aspect ratio) and behavior (defensive stinger usage). We also found a correlation between two aspects of morphology: pincer finger length correlates with the relative “thickness” (aspect ratio) of the metasoma. This suggests scorpions show a trade-off between their two main weapon complexes: the metasoma carrying the stinger, and the pedipalps carrying the chelae.